The Mediterranean diet : an evidence-based approach - Preedy, Victor R.; Watson, Ronald R. (Ronald Ross) (Amsterdam : Academic Press, an imprint of Elsevier, 2015)
The Mediterranean Diet offers researchers and clinicians a single authoritative source which outlines many of the complex features of the Mediterranean diet: ranging from supportive evidence and epidemiological studies, to the antioxidant properties of individual components. This book embraces a holistic approach and effectively investigates the Mediterranean diet from the cell to the nutritional well-being of geographical populations. This book represents essential reading for researchers and practicing clinicians in nutrition, dietetics, endocrinology, and public health, as well as research.
The Mediterranean diet: Concepts and general aspects -- Components of the Mediterranean diet -- Heath and nutritional aspects of the Mediterranean diet -- Novel nutraceuticals and edible plants used in the Mediterranean Region.
Includes bibliographical references and index.
Keywords: Diet -- Mediterranean Region; Dietetics; Nutrition